Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors

Calculator Output

Simplifying
fx + 3y = 2z

Solving
fx + 3y = 2z

Move all terms containing x to the left, all other terms to the right.

Add '-3y' to each side of the equation.
fx + 3y + -3y = -3y + 2z

Combine like terms: 3y + -3y = 0
fx + 0 = -3y + 2z
fx = -3y + 2z

Divide each side by 'f'.
x = -3f-1y + 2f-1z

Simplifying
x = -3f-1y + 2f-1z
Processing time: 1 ms. 51811411 equations since February 08, 2004.   Disclaimer

Equation Calculator & Solver

Equation: Variable:
       
Hint: Selecting "AUTO" in the variable box will make the calculator automatically solve for the first variable it sees.

Home Lessons Calculators Worksheets Resources Feedback Algebra Tutors